Current Status of Acute Stroke Management in Korea: A Report on a Multicenter, Comprehensive Acute Stroke Registry. Issue 4 (June 2014) - Kim, Beom Joon; Han, Moon-Ku; Park, Tai Hwan; Park, Sang-Soon; Lee, Kyung Bok; Lee, Byung-Chul; Yu, Kyung-Ho; Cha, Jae Kwan; Kim, Dae-Hyun; Lee, Jun; Lee, Soo Joo; Ko, Youngchai; et al.
There are limited data on the utilization of diagnostics and the variation of treatments at the national level in acute stroke care. Clinical Research Center for Stroke – 5th division stroke registry aimed to describe stroke statistics and quality of care in Korea and to implement quality indicators. Clinical Research Center for Stroke – 5th division registry was established in April 2008 and covers pretreatment demographics, medical and stroke severity measures, diagnostic evaluation, hyperacute revascularization, in-hospital management, discharge disposition, quality indicators, and long-term functional outcomes. Consecutive stroke cases from 12 participating centers are registered to a web-based database. Meticulous data management and auditing policy were applied. A total of 14 792 ischemic stroke cases were enrolled from April 2008 to January 2012. The median National Institutes of Health Stroke Scale score was 4 at admission, with median delay of onset to arrival of 14 h. Rate of risk factor management before stroke exceeds more than 80% for hypertension and diabetes. Revascularization procedures were performed in 1736 subjects (12%), and 34% were endovascular ( n = 598). Substantial variability was noted in the preferred modality of hyperacute revascularization (range of endovascular recanalization = 6–60%), use of computed tomography (30–93%), and perfusion imaging (2–96%). The Clinical Research Center for Stroke – 5th division registry documented that the current practice of acute stroke care in South Korea largely met the standard of guidelines, but variability of practice still remains. The registry would provide an opportunity to evaluate the quality of stroke care across South Korea and compare it with that of other countries.